The Policy of Ethnic Enclosure : A Study of the Role of Language in Ethnic Rivalries in the Caucasus - Rouvinski, Vladimir (Hiroshima University, 2007)
The lines from the poem Valerik that open this publication were write by the Russian poet Michael Lermontov in the year 1840, half of which he spent in the Caucasus before being shot to death in a duel just a year later. Sent to serve in the Russian imperial army fighting Caucasian highlanders, the poet had to participate in several harsh combats. Shocked by the cruelty of the war, he was also stunned by a long history of confrontation and bloodshed exerienced by the people of the Caucasus.
Keywords: Unión Soviética - Aspectos políticos; Conflicto; Historia politica; Cáucaso; Ciencia política; Social sciences